Cross-Task Compatibility and Age-Related Dual-Task Performance. - Grabbe, Jeremy W.; Allen, Philip A. (Experimental Aging Research)
Background/Study Context: This study examined the effects of stimulus-stimulus and response-response cross-task compatibility and aging on dual-task performance. Hypothesis 1 predicted that the response code compatibility effect in both experiments would benefit older adults comparably to younger adults. Hypothesis 2 predicted that stimulus-stimulus compatibility would be additive to the effects of cross-task compatibility. Methods: Younger and older adults participated in two dual-task experiments. Experiment 1 utilized a cross-task compatibility design identical to that of Koch and Prinz (2002, Journal of Experimental Psychology: Human Perception and Performance, 28, 192–201). Experiment 2 added a stimulus-stimulus compatibility condition. Results: The results of both experiments supported Hypothesis 1. Older adults displayed comparable cross-task compatibility effects to younger adults. The data did not support Hypothesis 2. The response-response compatibility effect from Experiment 1 was replicated, but the effect of stimulus-stimulus compatibility was not significant. Conclusion: The results of both experiments showed that older adults were able to take advantage of cross-task compatibility as a task design to improve dual-task performance. The lack of stimulus-stimulus compatibility effects in Experiment 2 suggested that the benefit of task design may be limited in effect.